Pengaruh Digitalisasi, Technostress, dan Motivasi Kerja terhadap Kinerja Pegawai Perumda Air Minum Tirta Ampera Kabupaten Boyolali - Etik Retno Wuryanti; Unna Ria Safitri; Alean Kistiani Hegy Suryana; Hari Purwanto (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
This research is designed to examine how digitalization, technostress, and work motivation influence employee performance within Perumda AM Tirta Ampera in Boyolali Regency. An explanatory quantitative approach was adopted as the research design. Utilizing the Slovin formula, a sample of 113 respondents was selected from a total population of 154 employees. Information was collected using questionnaires and subsequently evaluated through multiple linear regression analysis utilizing SPSS software. Classical assumption testing confirmed that the regression model is valid and free from heteroscedasticity and autocorrelation issues. Partially (t-test), digitalization exerts no significant effect on employee performance (Sig. 0.714 > 0.05), and similarly, technostress shows no significant influence (Sig. 0.729 > 0.05). Meanwhile, work motivation is proven to exert a significant positive contribution to employee performance (; Sig. ). Based on the simultaneous testing (F-test), these three independent aspects collectively demonstrate a significant effect in stimulating employee performance enhancement (; Sig. ). Furthermore, the coefficient of determination () value of 0.404 indicates that 40.4% of the variance in work performance can be explained by the combination of independent variables, while the remaining 59.6% is influenced by other factors outside the scope of this research model.